Positive Effect of Cognitive Reserve on Episodic Memory, Executive and Attentional Functions Taking Into Account Amyloid-Beta, Tau, and Apolipoprotein E Status - Narbutas, Justinas; Chylinski, Daphne; Van Egroo, Maxime; Bahri, Mohamed Ali; Koshmanova, Ekaterina; Besson, Gabriel; Muto, Vincenzo; Schmidt, Christina; Luxen, André; Balteau, Evelyne; Phillips, Christophe; Maquet, Pierre; et al. (Frontiers in Aging Neuroscience, 2021)
Studies exploring the simultaneous influence of several physiological and environmental factors on domain-specific cognition in late middle-age remain scarce. Therefore, our objective was to determine the respective contribution of modifiable risk/protective factors (cognitive reserve, allostatic load) on specific cognitive domains (episodic memory, executive functions, attention), taking into account non-modifiable factors (sex, age, genetic risk for AD) and Alzheimer’s Disease (AD) related biomarker amount (amyloid-beta, tau/neuroinflammation) in a healthy late middle-aged population. One hundred and one healthy participants (59.4 ± 5 y; 68 women) were evaluated for episodic memory, executive and attentional functioning via neuropsychological test battery. Cognitive reserve was determined by the National Adult Reading Test. Allostatic load consisted in measures of lipid metabolism and sympathetic nervous system functioning. Amyloid-beta level was assessed using Positron Emission Tomography (PET) in all participants, while tau/neuroinflammation PET scans and Apolipoprotein E (APOE) genotype were available for 58 participants. Higher cognitive reserve was the main correlate of better cognitive performance across all domains. Moreover, age was negatively associated with attentional functioning, whereas sex was a significant predictor for episodic memory, with women having better performance than men. Finally, our results did not show clear significant associations between performance over any cognitive domain and APOE genotype and AD biomarkers. This suggests that domain-specific cognition in late healthy midlife is mainly determined by a combination of modifiable (cognitive reserve) and non-modifiable factors (sex, age), rather than by AD biomarkers and genetic risk for AD.